2017
DOI: 10.4172/2472-0895.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Seizures: Incidence, Etiologies, Clinical Features and EEG Findings in the Neonatal Intensive Care Unit

Abstract: Objective: To evaluate the incidence, etiologies, clinical features and EEG findings of seizures among the neonates admitted to one medical center. Method:We retrospectively reviewed the medical records of neonates who were diagnosed to have neonatal seizure at the Neonatal Intensive Care Unit (NICU) of one medical center in Taiwan from January to December 2015. The clinical pictures, laboratory data, image and EEG findings were reviewed in all cases.Results: Neonatal seizures were diagnosed in 22 among 122 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is much lower than that reported by Sharek et al (4) that were 5.1% and that reported by Glass, (30) , as seizures rate ranged between 1 to 5 per 1000 live births. A study done in 2017 by Hu et al (31) revealed that seizures were 18.32%. Pisani et al (32) reported neonatal seizures were 2.29 per 1000 live births.…”
Section: Discussionmentioning
confidence: 98%
“…It is much lower than that reported by Sharek et al (4) that were 5.1% and that reported by Glass, (30) , as seizures rate ranged between 1 to 5 per 1000 live births. A study done in 2017 by Hu et al (31) revealed that seizures were 18.32%. Pisani et al (32) reported neonatal seizures were 2.29 per 1000 live births.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5] Main causes for NS include hypoxic ischemic encephalopathy, intracranial hemorrhage, stroke, intracranial infection, and metabolic disorders. [6][7][8][9][10] Since NS carry a major risk for death (up to 20%) or subsequent neurological disability, 11 it is crucial to identify risk factors associated with a higher risk for NS. The identification of such risk factors, whether modifiable or not, can allow the medical staff and public health scholars and policymakers to better predict populations at risk and to work toward tackling modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%